2020
DOI: 10.3390/en13143638
|View full text |Cite
|
Sign up to set email alerts
|

Steam Explosion Pretreatment of Beechwood. Part 2: Quantification of Cellulase Inhibitors and Their Effect on Avicel Hydrolysis

Abstract: Biomass pretreatment is a mandatory step for the biochemical conversion of lignocellulose to chemicals. During pretreatment, soluble compounds are released into the prehydrolyzate that inhibit the enzymatic hydrolysis step. In this work, we investigated how the reaction conditions in steam explosion pretreatment of beechwood (severity: 3.0–5.25; temperature: 160–230 °C) influence the resulting amounts of different inhibitors. Furthermore, we quantified the extent of enzyme inhibition during enzymatic hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…Some volatile substances were identified by the GC-MS analysis. The GC-MS analysis confirmed the presence of vanillin and syringaldehyde in the chloroform-ethanol extract, which are known products of lignin decomposition during biomass pretreatment (Jӧnsson and Martín 2016;Brethauer et al 2020). The results of GC-MS analysis are presented in Table 3 and discussed later in this paper.…”
Section: Chemical Composition Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…Some volatile substances were identified by the GC-MS analysis. The GC-MS analysis confirmed the presence of vanillin and syringaldehyde in the chloroform-ethanol extract, which are known products of lignin decomposition during biomass pretreatment (Jӧnsson and Martín 2016;Brethauer et al 2020). The results of GC-MS analysis are presented in Table 3 and discussed later in this paper.…”
Section: Chemical Composition Analysissupporting
confidence: 52%
“…In turn, the glucose content ranged from 3.7 to 23.2 mg/g native biomass and cellobiose from 2.1 to 9.8 mg/g native biomass. According to the results obtained by Brethauer et al (2020), the xylose also was a dominant sugar released to a liquid fraction. As a result of SE pretreatment, the maximal yield of 30 mg/g beech wood was reached at 180 °C.…”
Section: Analysis Of Released Sugars and Inhibitorsmentioning
confidence: 90%
“…Natural beechwood is a natural wood of medium hardness and softness, which has broad leaves and deciduous leaves and produces seeds, and its growth is prolonged, making soft hardwood. We chose the beech tree, a type of impact-resistant wood characterized by its lightweight and low cost . We took six cylindrical samples 20 × 20 cm from different pieces of this wood, using an automatic cutting machine with high accuracy (Figure S5).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…We chose the beech tree, a type of impact-resistant wood characterized by its lightweight and low cost. 42 We took six cylindrical samples 20 × 20 cm from different pieces of this wood, using an automatic cutting machine with high accuracy ( Figure S5 ). Figure 2 b shows the samples selected before and after automatic slicing.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Feedstock properties, ethanol titer and yield were assumed to be the same as in the base case in order to calculate the net savings by using CBP. The pretreatment was changed to a pure steam pretreatment instead of a dilute acid-catalyzed steam pretreatment used in the base case, because previous studies have successfully shown that steampretreated lignocellulose can be converted by consortium-based CBP and the CBP parameters are based on the available experimentally derived data with steam gun pretreatment [17,29,30]. The necessary, specific membrane surface was set to 10 m 2 /m 3 reactor volume.…”
Section: Process Parameters Of the Consortium-based Cbpmentioning
confidence: 99%